Acesso a medicamentos essenciais em farmácias e drogarias do Município de Araraquara - Ferreira-Filho, J. C R [UNESP]; Correia, G. T. [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (My University, 2010)
A survey to determine the availability of 20 essential medicines for the diseases with highest prevalence in primary health care was conducted in the city of Araraquara. The presence and the price of these medicines in private sector pharmacies and drugstores of the city were recorded. Two forms, recommended by the WHO, were used in the survey, one for availability and the other for prices. The drugs most commonly available in pharmacies and drugstores were: propranolol (90.5%), captopril (96%) and ranitidine (96%), while the least available were ferrous sulfate (27%), beclomethasone (33.8%) and ibuprofen (41.9%). The drugs that showed the greatest variation among the prices charged were: propranolol (97.1%), hydrochlorothiazide (96.4%) and glibenclamide (95.0%), while the least variable were salbutamol (30.8%) and trimethoprim-sulfamethoxazole (30.2%). Generic drugs, which were half (10) of those assessed, had the lowest prices. The indicators of access, referring to the ability of patients to acquire drugs for the treatment of major diseases at the primary health care level, showed that no establishment stocked all 20 essential drugs and that wide variations existed in their prices, undermining their availability to drug users, whose only sources are pharmacies and drugstores. These data demonstrate the importance of the popular pharmacy to improve the access to medicines, by lowering the cost and increasing the availability of the items selected for the National List of Essential Drugs (RENAME).

O levantamento teve como objetivo avaliar a disponibilidade de 20 medicamentos essenciais para doenças importantes da atenção básica a saúde, pela presença e o preço nas as farmácias e drogarias do setor privado do município de Araraquara/SP. O estudo foi realizado utilizando-se dois formulários, preconizados pela OMS, um para disponibilidade e outro para os preços. Os medicamentos mais disponíveis nas farmácias e drogarias foram o propranolol (90,5%), captopril (96%) e ranitidina (96%), e os menos disponíveis foram sulfato ferroso (27%), beclometasona (33,8%) e ibuprofeno (41,9%). Os medicamentos que apresentaram maior variação entre os preços praticados foram propranolol (97,1%), hidroclorotiazida 96,4% e glibenclamida (95,0%), e os de menor variação foram salbutamol (30,8%) e sulfametoxazol + trimetoprima (30,2%). Metade dos medicamentos avaliados (10) o menor preço era do medicamento genérico. Os indicadores de acesso por capacidade de aquisição para o tratamento das principais doenças no nível de atenção básica demonstrou que nenhum estabelecimento continha todos os medicamentos avaliados e evidenciaram grandes variações de preços, comprometendo o seu acesso aos usuários que a única forma de adquiri-los é em farmácias e drogarias. Palavras-chave: Preço de medicamento. Economia Farmacêutica. Medicamentos Genéricos.Farmacoepidemiologia.
Access to essential drugs in pharmacies and drugstores in the City of Araraquara
Keywords: Drug price; Drugs, generic; Economics, pharmaceutical; Pharmacoepidemiology; amoxicillin; bacitracin; beclometasone; captopril; cotrimoxazole; dexamethasone; digoxin; essential drug; ferrous sulfate; glibenclamide; hydrochlorothiazide; ibuprofen; mebendazole; metronidazole; neomycin; nystatin; oral contraceptive agent; paracetamol; propranolol; ranitidine; salbutamol; drug bioavailability; drug cost; pharmacoepidemiology; pharmacy; world health organization